CHALLENGES IN DATA SECURITY: TECHNOLOGICAL AND REGULATORY CHALLENGES IN THE PROTECTION OF PERSONAL DATA IN THE DIGITAL ERA - Asnawi, Muhamad Fuat; Muhammad Alif Muwafiq Baihaqy; Saifu Rohman; Nur Hasanah; Dian Asmarajati (Nacreva Publisher, 2025)
This study examines the challenges of personal data security in the digital era, focusing on encryption technology and the role of artificial intelligence (AI) in protecting personal data in an increasingly complex digital environment. Adopting a Systematic Literature Review (SLR) method, this study examines 91 articles obtained from IEEE Xplore and ScienceDirect to identify trends and challenges in personal data security, particularly in the context of cloud computing and the Internet of Things (IoT). The results show that although encryption technology and AI offer advanced solutions, major challenges remain in the implementation of global regulations such as GDPR and differences in policies and infrastructure across countries. This study also discusses potential solutions such as blockchain and the implementation of adaptive encryption to address weaknesses in personal data security.